The MIL-125(Ti)/Co3O4 towards efficiently removing tetracycline by synergistic adsorption-photocatalysis roles - Qiuyang Dai; Guicheng Gao; Jijun Tang; Rongfei Jiang; Shijiao Sun; Yonglin Ye; Shiyun Li; Rong Xie; Jiaoxia Zhang (Materials & Design)
The efficient removal of antibiotic residues from water has become a significant concern in environmental management. This study addresses the low tetracycline removal efficiency of MIL-125(Ti) due to its limited adsorption capacity and weak ultraviolet light absorption. To enhance the photocatalytic performance of MIL-125(Ti), Co3O4 with a suitable band gap was selected for designing and preparing the heterojunction catalyst. By leveraging the porous nature of metal–organic frameworks, Co3O4 was derived from ZIF-67(Co) to provide additional adsorption sites. Notably, the addition of just 0.5 % Co3O4, which exhibits negligible photocatalytic activity on its own, enabled MIL-125(Ti) to form a visible-light responsive Z-scheme heterojunction with superior adsorption capacity. The adsorption of tetracycline increased from 18.1 % for MIL-125(Ti) to 34.3 % for the MIL-125(Ti)/Co3O4 composite. Furthermore, the photocatalytic degradation rate of tetracycline increased from 41.1 % for MIL-125(Ti) to 57.6 % for MIL-125(Ti)/Co3O4, resulting in a remarkable overall tetracycline removal efficiency of 91.9 % due to the combined effects of adsorption and photocatalysis. The Z-scheme heterojunction demonstrated excellent stability and reusability after undergoing five cycles. This study provides new insights into the design of MIL-125(Ti)-based composites for efficient synergistic adsorption and photocatalysis.